Individualized internal and external training load relationships in elite wheelchair rugby players - Paulson, T. A. W.; Mason, B.; Rhodes, J.; Goosey-Tolfrey, V. L. (Frontiers in Physiology, 2016)
Aim: The quantification and longitudinal monitoring of athlete training load (TL) provides a scientific explanation for changes in performance and helps manage injury/illness risk. Therefore, accurate and reliable monitoring tools are essential for the optimization of athletic performance. The aim of the present study was to establish the relationship between measures of internal [heart rate (HR) and session RPE (sRPE)] and external TL specific to wheelchair rugby (WR).